2017
DOI: 10.1007/s11356-017-8687-0
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry: a sustainable environmental practice for carbon sequestration under the climate change scenarios—a review

Abstract: Agroforestry is a sustainable land use system with a promising potential to sequester atmospheric carbon into soil. This system of land use distinguishes itself from the other systems, such as sole crop cultivation and afforestation on croplands only through its potential to sequester higher amounts of carbon (in the above- and belowground tree biomass) than the aforementioned two systems. According to Kyoto protocol, agroforestry is recognized as an afforestation activity that, in addition to sequestering car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(78 citation statements)
references
References 154 publications
4
71
0
3
Order By: Relevance
“…Policies for mitigation and adaptation to climate changes should improve sustainable strategies aimed at the most effective use of natural resources close to areas with high human pressure [37,42,46,[94][95][96]. Approaches based on long-term climate forecasts and integrated with local-scale analysis of spatial variability in climate trends provide meaningful information to scenario investigation for future stability of peri-urban natural and agricultural environments in the Mediterranean basin [31,[97][98][99][100][101][102][103][104]. Rome's expansion was assessed in the last years by focusing on the spatial demographic dynamics and the decline of the agricultural sector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Policies for mitigation and adaptation to climate changes should improve sustainable strategies aimed at the most effective use of natural resources close to areas with high human pressure [37,42,46,[94][95][96]. Approaches based on long-term climate forecasts and integrated with local-scale analysis of spatial variability in climate trends provide meaningful information to scenario investigation for future stability of peri-urban natural and agricultural environments in the Mediterranean basin [31,[97][98][99][100][101][102][103][104]. Rome's expansion was assessed in the last years by focusing on the spatial demographic dynamics and the decline of the agricultural sector.…”
Section: Discussionmentioning
confidence: 99%
“…Rome's expansion was assessed in the last years by focusing on the spatial demographic dynamics and the decline of the agricultural sector. Implications of global/local warming on peri-urban agriculture should be further investigated with the final objective to inform municipalities' policies supporting a sustainable land management [47,96,[104][105][106][107][108][109].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac sections were stained for fibrosis with picrosirius red (WT, n = 5; TLR9 KO, n = 5; SERCA2a KO, n = 22; and SERCA2a/TLR9 KO, n = 13) as previously described [16]. For optimal visualization of picrosirius red-positive tissue, haematoxylin staining was excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Quandt et al [12] also found agroforestry was a key adaptation strategy to climate change in Sub-Saharan Africa (SSA). Further, the reports of Abbas et al [7], Coulibaly et al [8], and Hunde [9] all confirmed agroforestry improves the biological productivity of crops for household food and nutritional security. While the literature provides the necessary evidence to invest in agroforestry as a climate-smart option, they are rather generalized, making it unclear as to how specific agroforestry technologies or practices such as improved fallows achieve the mitigation, adaptation and productivity goals of CSA.…”
Section: Introductionmentioning
confidence: 93%
“…With woody perennials as integral components, improved fallows fall under the category of landscape-scale mitigation schemes under the REDD+ (Reduction Emissions from Deforestation and forest Degradation) and AFOLU (Agriculture, Forestry, and other land uses) concepts [5]. In the literature, a lot is discussed about how agroforestry as an umbrella term for land use systems integrating trees with crops and/or animals achieves the mitigation, adaptation and productivity goals of climate-smart agriculture (CSA) [7][8][9][10]. For instance, Kim et al [11] reported agroforestry mitigates 27 ± 14 t CO 2 equivalent ha −1 year −1 , which is significant to reducing global carbon emissions.…”
Section: Introductionmentioning
confidence: 99%